Effects of age on parathyroid hormone signaling in human marrow stromal cells - Zhou, Shuanhu; Bueno, Ericka M.; Kim, Sung Won; Amato, Ilaria; Shen, Longxiang; Hahne, Jochen; Bleiberg, Ilan; Morley, Paul; Glowacki, Julie (Aging cell, 2011)
Summary Human bone marrow stromal cells (hMSCs) have the potential to differentiate into osteoblasts; there are age‐related decreases in their proliferation and differentiation to osteoblasts. Parathyroid hormone (PTH), when applied intermittently in vivo, has osteoanabolic effects in a variety of systems. In this study, we compared PTH signaling and osteoanabolic effects in hMSCs from young and old subjects. There were age‐related decreases in expression of PTH/PTHrP receptor type 1 (PTHR1) gene (P = 0.049, n = 19) and in PTH activation of CREB (P = 0.029, n = 7) and PTH stabilization of β‐catenin (P = 0.018, n = 7). Three human PTH peptides, PTH1‐34, PTH1‐31C (Ostabolin‐C, Leu27, Cyclo[Glu22‐Lys26]‐hPTH1‐31), and PTH1‐84 (10 nm), stimulated osteoblast differentiation with hMSCs. Treatment with PTH1‐34 resulted in a significant 67% increase in alkaline phosphatase activity in hMSCs obtained from younger subjects (<50 years old, n = 5), compared with an 18% increase in hMSCs from elders (>55 years old, n = 7). Both knockdown of CREB and treatment with a protein kinase A inhibitor H‐89 blocked PTH stimulation of osteoblast differentiation in hMSCs from young subjects. The PTH peptides significantly stimulated proliferation of hMSCs. Treatment with PTH1‐34 resulted in an average of twice as many cells in cultures of hMSCs from young subjects (n = 4), but had no effect with hMSCs from elders (n = 7). Upregulation of PTHR1 by 24‐h pretreatment with 100 nm dexamethasone rescued PTH stimulation of proliferation in hMSCS from elders. In conclusion, age‐related intrinsic alterations in signaling responses to osteoanabolic agents like PTH may contribute to cellular and tissue aging of the human skeleton.